STUDY OF PROGRESSIVE FREEZE CONCENTRATION IN BIODIESEL WASTEWATER VOLUME REDUCTION - HZIEN HUNG, SIEW (IRC, 2017)
Wastewater management has the most direct impact on the biological diversity of aquatic ecosystem. Wastewater treatment shall remove and separate waste from water so that the amount of waste can be reduced. Progressive freeze concentration is proposed to improve the existing treatment for wastewater as its main purpose is to remove and separate water from wastewater so that the volume of waste can be reduced. This method is beneficiary as it helps to reduce the cost of waste transportation to the next treatment. Water extracted from the waste could be recycled or drained out to the environment without causing more pollution. This research aims to observe the possibility of using progressive freeze concentration (PFC), one of the crystallization technology to remove water from wastewater produced during biodiesel purification. Relevant parameters like temperature and stirring rate were studied to evaluate the efficiency of the process and the purity of treated wastewater. The performance of progressive freeze concentration was assessed through the final concentration of concentrated wastewater and purity of melted ice crystals using refractometer. The final findings of the best parameter combination is temperature at -15oC to -20oC and a stirring rate range of 350 rpm to 550 rpm.